2020
DOI: 10.3390/ijerph17020590
|View full text |Cite
|
Sign up to set email alerts
|

Relations among Poly-Bullying Victimization, Subjective Well-Being and Resilience in a Sample of Late Adolescents

Abstract: The present study examined the relations among poly-bullying victimization (experiencing multiple forms of peer bullying), resilience and subjective well-being. This study specifically examined late adolescents’ resilience as a moderator of the relation between poly-bullying victimization and subjective well-being. In a region of central Spain, 1430 undergraduate students (64% females, 36% males), aged between 18 and 22 years, completed three self-reported measures, including bullying victimization experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 70 publications
3
31
1
3
Order By: Relevance
“…Consistent with this, it is used as a key outcome in several fields of psychology and mental health [ 33 ]. Even though most studies examining subjective wellbeing have traditionally focused on adult populations, recent years have witnessed an upsurge of interest in the role of subjective wellbeing for adolescent health and development [ 34 , 35 , 36 , 37 , 38 ]. In particular, during normative adolescence, attaining high levels of subjective wellbeing may reflect a successful and constructive psychosocial adjustment to one of the most rapid phases of human development [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, it is used as a key outcome in several fields of psychology and mental health [ 33 ]. Even though most studies examining subjective wellbeing have traditionally focused on adult populations, recent years have witnessed an upsurge of interest in the role of subjective wellbeing for adolescent health and development [ 34 , 35 , 36 , 37 , 38 ]. In particular, during normative adolescence, attaining high levels of subjective wellbeing may reflect a successful and constructive psychosocial adjustment to one of the most rapid phases of human development [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Offline DV victimization in a romantic relationship negatively affects adolescents' well-being and has been related to stress, anxiety, less satisfaction with life, poor academic achievement, low self-esteem, substance abuse, and eating disorders [30,31,33,36,37]. Positive correlations among different forms of offline DV victimization (physical, verbal-emotional, and relational) have been observed [38], and it has also been suggested that being victimized in one social context increases the probability of being victimized in other social contexts, which could increase the possibility of suffering poly-victimization [39][40][41][42][43][44]. However, no study has yet explored if different forms of offline DV victimization, such as physical, verbal-emotional or relational victimization, have varying predictive weights in relation to distinct forms of cyber DV victimization: cyber-control and cyber-aggression.…”
Section: Offline and Cyber Dating Violence Victimizationmentioning
confidence: 99%
“…Previous studies have linked CDV victimization with depressive symptoms [9,28], anxiety [28], suicide risk [7], emotional/psychological distress and low self-esteem [15,36]. However, some researchers have suggested that adolescents' perception of some abusive behaviors as normal behaviors in a romantic relationship can minimize these negative outcomes [41,42]. Cyber-control victimization, especially when it is occasional, may not be perceived as CDV victimization by adolescents and could be less related to problems in adolescents' psychosocial adjustment.…”
Section: Cyber Dating Violence Victimization Depressive Mood and Lonelinessmentioning
confidence: 99%
“…One interesting question to examine is the possible connections between being victimized by both cyberbullying and CDV. Adolescent victims in one interpersonal context are more probable to also be victimized in other interpersonal contexts or through other forms of victimization, and they can suffer situations of poly-victimization [42,43,51,52]. The connection between teen dating violence victimization and peer victimization [39,43,[53][54][55][56][57], and the links between offline and online dating violence victimization [11,22,27,39], have been pointed out.…”
Section: Cyber Dating Violence Victimization and Cyberbullying Victimizationmentioning
confidence: 99%